Effects of Oral Appliance Therapy with a Mouth Shield in Periodontitis Patients Who Snore: A Split-Mouth Randomized Controlled Trial - Ju-Ying Lin; Emet Schneiderman; Jason Hui; Carlos Parra Carrasquer; William Stenberg; Zohre German; Jason Adam Harvey; Preetam Schramm (Dentistry Journal)
Background: Periodontitis is linked to sleep-disordered breathing (SDB), including snoring, with 50–75% of cases involving mouth breathing (MB). Standard treatment includes scaling and root planing (SRP). Oral appliance therapy (OAT) is used to treat snoring and SDB. OAT plus a mouth shield (OAT+) worn during sleep may reduce MB to enhance periodontal health. This study evaluated whether OAT+, as an adjunct to SRP, improves periodontal health by reducing periodontal pathogens and facilitating upper airway patency. Methods: Fourteen participants with mild–moderate periodontitis were randomized to receive SRP on one side of the mouth at baseline (T0). Pocket depth (PD), bleeding on probing (BOP), and plaque index (PI) were recorded, and bacterial DNA from periodontal pockets were analyzed via PCR at baseline (T0) and 12 weeks (T3). At 4 weeks (T1), all participants received a self-titrated myTAP® OA, followed by a mouth shield at 8 weeks (T2). Sleep metrics, including respiratory disturbance index (RDI), were recorded using the NOX T3 at T0–T3. Results: BOP and deep PD levels exhibited slight improvements from the baseline for both SRP and non-SRP (OAT+ only) treated sites but did not achieve significance. BOP decreased significantly more from the baseline in the SRP than in the non-SRP group at T3 (p = 0.028); P. gingivalis’ presence declined on both sides (p = 0.0135). Other periodontal and bacterial parameters showed no significant differences between or within groups. Snoring (p = 0.011), MB (p = 0.025), and RDI (p = 0.019) significantly decreased with OAT+ at T3. Conclusions: In mild–moderate periodontitis patients who snore, OAT+ reduces snoring, MB, and obstructive events, serving as an adjunct to SRP with no negative clinical effects over the short term. The combined therapy yielded similar results to OAT+ alone, likely due to minimization of MB. Its capacity to improve the oral environment is worthy of further investigation.